Economywide impact of avian flu in Ghana: A dynamic CGE model analysis - Diao, Xinshen (International Food Policy Research Institute, 2009)
The primary goal of this paper is to provide a quantitative assessment of the economywide impact of HPAI in Ghana under different scenarios. A dynamic computable general equilibrium (DCGE) model for Ghana has been developed for this study, and a recent (2005) social accounting matrix with a detailed production structure at both national and sub-national levels is used as the dataset for this analysis.